Angular momentum synergies during walking - Robert, Thomas; Bennett, Bradford C; Russell, Shawn D; Zirker, Christopher A; Abel, Mark F (Experimental brain research, 2009)
We studied the coordination of body segments during treadmill walking. Specifically, we used the uncontrolled manifold hypothesis framework to quantify the segmental angular momenta (SAM) synergies that stabilize (i.e., reduce the across trials variability) the whole body angular momentum (WBAM). Seven male subjects were asked to walk over a treadmill at their comfortable walking speed. A 17-segment model, fitted to the subject's anthropometry, was used to reconstruct their kinematics and to compute the SAM and WBAM in three dimensions. A principal component analysis was used to represent the 17 SAM by the magnitudes of the first five principal components. An index of synergy (ΔV) was used to quantify the co-variations of these principal components with respect to their effect on the WBAM. Positive values of ΔV were observed in the sagittal plane during the swing phase. They reflected the synergies among the SAM that stabilized (i.e., made reproducible from stride to stride) the WBAM. Negative values of ΔV were observed in both frontal and sagittal plane during the double support phase. They were interpreted as “anti-synergies”, i.e., a particular organization of the SAM used to adjust the WBAM. Based on these results, we demonstrated that the WBAM is a variable whose value is regulated by the CNS during walking activities, and that the nature of the WBAM control changed between swing phase and double support phase. These results can be linked with humanoid gait controls presently employed in robotics.